Enhancing Data Governance in Higher Education Using the COBIT 2019 Framework for Strategic IT Alignment - Muhamad Rodi; Khairul Imtihan; Mardi Mardi; Wire Bagye; Amrullah Amrullah; Baiq Yulia Fitriyani (JiTEKH, 2026)
The rapid evolution of digital technology has increased the need for structured data governance within higher education institutions (HEIs) to ensure effective strategic IT alignment. This study examines the application of the COBIT 2019 framework as a governance mechanism to assess and enhance data governance maturity in an academic environment. A case study approach was employed at Campus X, an Indonesian higher education institution specializing in informatics and information systems. Data were collected through semi-structured interviews, questionnaires using a five-point Likert scale, and document analysis. The results indicate that the overall IT governance maturity level at Campus X is moderate, with an average score of 3.0 out of 5.0. Specifically, the APO12 (Strategic IT Alignment) domain achieved a maturity score of 2.5, while the MEA03 (Evaluation and Audit) domain recorded the lowest score at 2.0, indicating weaknesses in strategic alignment and governance evaluation processes. In contrast, the DSS03 (Service Delivery) domain demonstrated a relatively high maturity level with a score of 4.0, reflecting well-established operational practices. These findings highlight critical gaps in aligning IT initiatives with institutional objectives and in implementing systematic monitoring and evaluation mechanisms. This study contributes to the literature by demonstrating how the COBIT 2019 framework can be adapted to the context of HEIs to improve data governance maturity. Practical recommendations include increasing senior management involvement, implementing real-time monitoring tools, and strengthening formal IT governance policies. The results provide empirical evidence that structured IT governance frameworks can support more effective data-driven decision-making and strategic IT alignment in higher education.